Comparison of an e-learning package with lecture-based teaching in the management of supraventricular tachycardia (SVT): a randomised controlled study. Issue 1157 (24th December 2020) - Mohee, Kevin; Haboubi, Hasan N; Protty, Majd; Srinivasan, Christopher; Townend, William; Weston, Clive
Abstract: Introduction: To compare the impact of an e-learning package with theoretical teaching on the ability of both graduate and undergraduate medical students to learn the management of supraventricular tachycardia. Methods: We conducted a randomised, controlled, study at two Welsh medical schools. Participants were graduate-entry and undergraduate medical students, who were randomised (in a 1:1 ratio) to either 1 hour of training using an e-learning package or an hour of lecture-based teaching. The outcome was a comparison, within each group and between groups, of median scores achieved in assessments of knowledge through completion of preintervention, immediate post intervention and 2 weeks postintervention questionnaires. Results: Of the 97 participants available for randomisation, 47 underwent teaching using the e-learning package and 50 were taught in the lecture group. Median scores were higher in the e-learning package group than the lecture group, though this difference was not statistically significant (4.00 vs 3.00; p=0.08) immediately after intervention. At 2 weeks post intervention, median scores in the e-learning package group were significantly higher than the median scores in the lecture group (4.00 vs 3.00; p=0.002). This was despite a subanalysis of the results demonstrating that subjects in the lecture group reported having seen more cases compared with those in the e-learning group (32 vs 13; p=0.002). Further, there was a significant fall in score over 2 weeks in the group receiving lecture-based teaching, but no such decrease in those using the e-learning package. Conclusion: E-learning seems to be the preferred method of learning and the method that confers longer retention time for both postgraduate and undergraduate medical students.